FAME 2: Simple and Effective Machine Learning Model of Cytochrome P450 Regioselectivity - Šícho, Martin; de Bruyn Kops, Christina; Stork, Conrad; Svozil, Daniel; Kirchmair, Johannes (Journal of chemical information and modeling, 2017)
UNLABELLED: We report on the further development of FAst MEtabolizer (FAME; J. Chem. Inf. MODEL: 2013, 53, 2896-2907), a collection of random forest models for the prediction of sites of metabolism (SoMs) of xenobiotics. A broad set of descriptors was explored, from simple 2D descriptors such as those used in FAME, to quantum chemical descriptors employed in some of the most accurate models for SoM prediction currently available. In line with the original FAME approach, our objective was to keep things simple and to come up with accurate and robust models that are based on a small number of 2D descriptors. We found that circular descriptions of atoms and their environments with such descriptors in combination with an extremely randomized trees algorithm can yield models that perform equally well compared to more complex approaches. Thorough evaluation experiments on an independent test set showed that the best of these models obtained a Matthews correlation coefficient, area under the receiver operating characteristic curve, and Top-2 accuracy of 0.57, 0.91 and 94.1%, respectively. Models for the prediction of isoform-specific regioselectivity of CYP 3A4, 2D6, and 2C9 were also developed and showed competitive performance. The best models have been integrated into a newly developed software package (FAME 2), which is available free of charge from the authors.
Keywords: xenobiotika; strojové učení; Computational Biology; Software; Substrate Specificity; výpočetní biologie; Stereoisomerism; software; Machine Learning; systém (enzymů) cytochromů P-450; Cytochrome P-450 Enzyme System; substrátová specifita; Xenobiotics; stereoizomerie